2021
DOI: 10.1097/01.aoa.0000766160.24091.89
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spinal Hypotension and Anesthesia-to-delivery Time Interval on Neonatal Outcomes in Planned Cesarean Delivery

Abstract: A natomic changes associated with pregnancy may render conduct of neuraxial procedures in parturients more difficult. The standard position for a neuraxial block requires a patient to sit on a bed with the spine flexed and legs supported on a stool, but spinal flexion may be improved by instead sitting cross-legged on the bed. Given the lack of prospective studies on this topic, the aim of this study was ultrasonographic assessment of the paramedian target area's size when a pregnant woman sits in the crossleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…The incidence of neonatal acidosis in our study is similar to what has been reported. 2 4 5 17 Unlike prior studies though, we did not find an association between spinal-induced hypotension and other adverse neonatal outcomes, nor did we find a significant difference in spinal-to-delivery time stratified by neonatal acidosis. The findings of our study may be due to tighter blood pressure control with the use of prophylactic vasopressor infusions, which became routine practice at our center in 2019.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The incidence of neonatal acidosis in our study is similar to what has been reported. 2 4 5 17 Unlike prior studies though, we did not find an association between spinal-induced hypotension and other adverse neonatal outcomes, nor did we find a significant difference in spinal-to-delivery time stratified by neonatal acidosis. The findings of our study may be due to tighter blood pressure control with the use of prophylactic vasopressor infusions, which became routine practice at our center in 2019.…”
Section: Discussioncontrasting
confidence: 99%
“…5 Knigin et al similarly reported that longer anesthesia-to-delivery times were significantly associated with increased risk for neonatal acidosis. 4 Hassanin et al found spinal-to-delivery time of >27 minutes to be predictive of a umbilical artery pH < 7.2 in their study cohort. 13 We did not find this association in our study cohort, perhaps because prophylactic vasopressors allow for optimal control of maternal blood pressures after spinal anesthesia, making time from spinal-to-delivery less important.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations